2015
DOI: 10.1002/2014jf003257
|View full text |Cite
|
Sign up to set email alerts
|

Modeling flow and sediment transport dynamics in the lowermost Mississippi River, Louisiana, USA, with an upstream alluvial‐bedrock transition and a downstream bedrock‐alluvial transition: Implications for land building using engineered diversions

Abstract: The lowermost Mississippi River, defined herein as the river segment downstream of the Old River Control Structure and hydrodynamically influenced by the Gulf of Mexico, extends for approximately 500 km. This segment includes a bedrock (or more precisely, mixed bedrock-alluvial) reach that is bounded by an upstream alluvial-bedrock transition and a downstream bedrock-alluvial transition. Here we present a one-dimensional mathematical formulation for the long-term evolution of lowland rivers that is able to rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 48 publications
1
54
0
Order By: Relevance
“…The observed spatial changes in water depth partially confirm the numerical predictions of the Viparelli et al () formulation, i.e., at equilibrium in a low slope bedrock reach downstream of an alluvial‐bedrock transition, the flow is characterized by a reduction of the flow depth in the streamwise direction. The experimental results however showed that the problem is more complex than in the Viparelli et al () formulation due to the changes in bedform geometry and grain size distribution of the alluvial bed surface, which can occur even with very small changes in flow depth and velocity.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…The observed spatial changes in water depth partially confirm the numerical predictions of the Viparelli et al () formulation, i.e., at equilibrium in a low slope bedrock reach downstream of an alluvial‐bedrock transition, the flow is characterized by a reduction of the flow depth in the streamwise direction. The experimental results however showed that the problem is more complex than in the Viparelli et al () formulation due to the changes in bedform geometry and grain size distribution of the alluvial bed surface, which can occur even with very small changes in flow depth and velocity.…”
Section: Resultssupporting
confidence: 80%
“…The results of Figures show that the response of the flow and of the bedload transport to the presence of an un‐erodible surface is more complex than that presented in Zhang et al () and Viparelli et al (). Notwithstanding the streamwise reduction of the flow resistances (Figures a, b, d, e, g, h, j, and k), downstream of the stable alluvial‐bedrock transitions, the bed material transport capacity tends to increase in the direction of the flow (Figure c, f, i, and l).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations